1990
DOI: 10.1088/0029-5515/30/10/011
|View full text |Cite
|
Sign up to set email alerts
|

Self-consistency of the principle of profile consistency results for sawtoothing tokamak discharges

Abstract: DISCLAIMERThis i-eport was prepared as an accouni of +ork sponsored hy an agency uf the United States Government Neither (he United Slates Government nor jn> agency thereof, nor any of their employees, makes any warranty, express or implied. 01 assume* any legal liability or responsihilili for the accuracy, completeness, or usefulness af any infocmauon, apparatus, product. 01 process disclosed, or represents that its use would not infringe privately owned rights Refer ence herein to any specific commercial pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 72 publications
(166 reference statements)
1
21
1
Order By: Relevance
“…ln[I p ] is clearly the most important control variable. This result contrasts with earlier profile consistency studies 12,17 which found that the edge safety factor, q 95 , is the most important variable in determining the temperature profile shape. This difference occurs because we are fitting the unnormalized temperature and I p is much more important than q 95 in determining the magnitude of the temperature.…”
Section: B) Model Selectioncontrasting
confidence: 99%
“…ln[I p ] is clearly the most important control variable. This result contrasts with earlier profile consistency studies 12,17 which found that the edge safety factor, q 95 , is the most important variable in determining the temperature profile shape. This difference occurs because we are fitting the unnormalized temperature and I p is much more important than q 95 in determining the magnitude of the temperature.…”
Section: B) Model Selectioncontrasting
confidence: 99%
“…͑1͒ describes in fact the monotonic variation of rational surfaces, 1/q s ϵm/n ͑m and n are, respectively, the poloidal and toroidal mode num-ber͒. In 1990, Arunasalam et al 8 presented an exhaustive study on the principle of profile consistency. But to this day the following questions raised by the three papers have remained unanswered:…”
Section: Introductionmentioning
confidence: 99%
“…Our research systematises and validates earlier graphical and qualitative studies of "profile consistency". (See [4] for a review of this topic.) The statistical approach enables us to make quantitative statements about the relative strength of the interior q a dependence and the weaker exterior parametric dependencies of the profile shape.…”
Section: Introductionmentioning
confidence: 99%